PENGARUH PENERAPAN PEMBELAJARAN KONTEKSTUAL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS XI MANBARUMUN TENGAH - Nur Hajijah Harahap (JURNAL MathEdu (Mathematic Education Journal), 2019)
ABSTRACT They aims of this study is to know whether there is a significant influence of applying contextual learning on student’s mathematical problem solving ability at the eleventh grade student’s of MAN Barumun Tengah. This research was contucted by applying experimental (one group pre test post test design) with 30 student’s and they were taken by using random sampling technique from 144 student’s. Observation and test were used in collecting they data. Based on descriptive analysis, it was found that : (a) the average of applying contextual learning was 3,5 ( very good category) and (b) the average of student’s mathematical problem solving ability before of applying contextual learning was 46.66 ( fair category) and after using of applying contextual learning was 71,2(good category). Furthermore, based on inferential statistic by using pair sample t tes SPSS version 16, it could found significant value was tess 0.05 (0.000<0.05). It means, there is they influence of applying contextual learning on student’s mathematical problem solving ability at the eleventh grade student’s of MAN Barumun Tengah. Keyword : applying contextual learning, student’s mathematical problem solving